Interference of Emotional Information in Briefly Presented Scene Arrays - Michaela Porubanova; Ryan Priefer (Studia Psychologica, 2019)
Research has shown that the presentation of emotional information interferes with the processing of neutral information. The present study examined whether one can suppress this interference when being asked to ignore an emotional scene before attention is engaged with a target or if emotional information always engages attention, resulting in attentional capture. We examined participants’ ability to actively inhibit emotional scenes of different valence and arousal when identifying neutral scenes. In three experiments, a 4-scene array was presented for 250 ms while one emotional scene was present in the display. The scene was either to be ignored or freely available in the array. The results show that the interference from emotional scenes is a pervasive phenomenon, suggesting an involuntary attentional capture by emotional scenes. Moreover, despite the vast literature on the evolutionary advantage of preferential processing of negative information, we show a potent attentional bias toward positive information.